Understanding the Patient Perception of Statin Experience: A Qualitative Study - Vrablik, Michal; Catapano, Alberico L; Wiklund, Olov; Qian, Yi; Rane, Pratik; Grove, Alyson; Martin, Mona L (Advances in therapy, 2019)
INTRODUCTION: Statin intolerance (SI) occurs in patients with dyslipidemia treated with statins. Statin-associated symptoms have been reported, but the overall patient experience is poorly understood. No instruments are available to collect this patient experience. Our aim is to develop a patient survey to define SI from the patient's perspective, inform clinical practice, and identify potential patient characteristics and barriers associated with discontinuing treatment when statin-related difficulties are encountered. METHODS: We conducted qualitative concept elicitation interviews with 65 patients across 12 European study sites. A semi-structured qualitative interview guide was developed based on literature review and clinician interviews. Concept elicitation interviews with patients were used to describe the patient experience and develop the conceptual framework for the survey. RESULTS: Symptoms experienced by patients included muscle and non-muscle-related pain and discomfort; other muscle-related symptoms; gastrointestinal, cardiovascular, cold-like, fatigue-related, and sensory and systems symptoms; mood changes; and cognitive and memory problems. Impacts included limitations on general physical functioning; physical activities; social functioning; emotional impacts; sleep disturbances; decreased productivity; and increased healthcare use. Conceptual framework elements to support survey goals include demographic and clinical characteristics, health information and beliefs, statin side-effect history, symptom severity, and impact severity. CONCLUSIONS: Symptoms and impacts described by patients showed a wider range of symptoms and impacts than usually discussed clinically. The patient survey is designed to capture information from patients who experience difficulties with statin therapy and may be useful in identifying patients who are at higher risk for giving up or discontinuing their treatment. FUNDING: Amgen Inc.
Keywords: spokojenost pacientů; dospělí; Qualitative Research; průzkumy a dotazníky; Female; Europe; Dyslipidemias; Adult; Patient Satisfaction; ženské pohlaví; Surveys and Questionnaires; anticholesteremika; lidé; Evropa; statiny; bolest; Anticholesteremic Agents; Male; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Aged; dyslipidemie; Pain; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kvalitativní výzkum; Humans